Relationship Between Gender Discrimination, Work-Life Balance and Mental Health: The Nigerian Female Educators’ Perspective - Ekene Ezinwa Nwankwo (IIARD INTERNATIONAL JOURNAL OF ECONOMICS AND BUSINESS MANAGEMENT, 2026)
This study examined relationship between gender discrimination, work-life balance and mental health: The Nigerian female educators’ perspective. Two specific purposes, two research questions and two hypotheses guided the study. Correlational design was adopted for the study. The population of the study comprised all the 10,009 female teachers in public secondary schools in Anambra State. The sample size was 1,001 female teachers drawn using proportionate stratified random sampling technique. Structured rating scales “Gender Discrimination Rating Scale (GDRS), Mental Health Rating Scale (MHRS) and Work-Life Balance Rating Scale (WLBRS)” were used for data collection. The instrument was face validated by three experts in Faculty of Education. Average internal consistency co-efficient of 0.87, 0.84 and 0.79 was obtained for GDRS, MHRS and WLBRS respectively using Cronbach Alpha statistical method. The researcher administered the instrument to the respondents with the help of four research assistants. Data were analyzed using Pearson Product Moment Correlation Coefficient. The p-value was used to determine the significance of relationship at a significance level of 0.05 (5%). The findings revealed that there is positive relationship between gender discrimination, work-life balance and mental health of female teachers in secondary schools in Anambra State. From the results of the hypotheses, significant relationship was established in all the variables of the study. The study concluded that as these women navigate systemic discrimination and the challenges of balancing personal and professional responsibilities, their mental health is significantly impacted. Based on the findings, the study recommended among others that education sector must adopt policies that promote gender equity and support work-life balance by reducing discriminatory practices and providing support for balancing personal and professional roles.